Pengaruh Pemberian Ekstrak Etanol Daun Kenikir (Cosmos caudatus Kunth.) terhadap Kerusakan Struktur Histologis Hepar Mencit (Mus musculus L.) yang Diinduksi Parasetamol - Alvian Oscar Irawan; . Suyatmi; Yulia Sari (Nexus Biomedika, 2014)
Background: Kenikir leaf contains flavonoids, phenolic acid, saponin, carotenoids, vitamin A, vitamin C, Fe, Zn, and Cu. They are potential antioxidants being capable of protecting cells from free radical. The aim of this research is to evaluate the hepatoprotective effect of kenikir (Cosmos caudatus Kunth.) leafs ethanol extract on mice induced by paracetamol. Methods: This research was a laboratory-based experiment with the post-test only with control group design. The samples of 35 male Swiss webster mice, aged 2-3 months with 20 gram of weight were randomly divided into 5 groups. The groups were normal group (KN), negative control group (KK(-)), treatment group 1 (KP1), treatment group 2 (KP2), and treatment group 3 (KP3). Extract dosage of 2.8 mg, 5.6 mg, and 11.2 mg were administered daily for 14 days to KP1, KP2 and KP3, respectively. A toxic dosage of paracetamol was administered to KK(-), KP1, KP2, and KP3 on day 12th, 13th, and 14th. On day 15th, mice were sacrificed by neck dislocation and the liver were prepared and stained with HE for histology study. The degree of damage being due to the paracetamol was based on summation of pyknosis, karyorrhexis, karyolysis nucleus. Data were analyzed using One-Way ANOVA test (? = 0.05), followed by Post Hoc Multiple Comparisons (LSD) (? = 0.05) test. Results: The One-Way ANOVA test result was p = 0.000 (p < ?). The statistical LSD test result was p = 0.000 (p < ?), which showed significant differences in the hepatic damage between KN-KK(-), KN-KP1, KN-KP2, KN-KP3, KK(-)-KP1, KK(-)-KP2, KK(-)-KP3, KP1-KP2, KP1-KP3, and KP2-KP3 group. Conclutions: The administration of kenikir leafs extract is able to prevent the damage in mices liver cells induced by paracetamol. Keyword: ethanol extract, kenikir (Cosmos caudatus Kunth.) leaf, paracetamol, liver cells, mice